United States of Tara. The complete series [videorecording (DVD)] - Cody, Diablo (CBS DVD, 2020)
Tara Gregson is a wife and mother with dissociative identity disorder (DID). After deciding to go off her medication to discover the real cause of her disorder, her alternate personalties re-emerge. T is a wild and flirty teenager; Alice is an old-fashioned housewife; and Buck is a male, loud, beer-drinking Vietnam Vet. Tara is supported by Max, her calm and level-headed husband; Kate, her somewhat troubled teenage daughter; and Marshall, her quirky, good-hearted gay son. Her sister, Charmaine, is not so supportive, often expressing her doubt about the validity of Tara's disorder.